Penggunaan Metode Jarimatika untuk Meningkatkan Hasil Belajar Penjumlahan pada Siswa Kelas II SDI Harekakae - Maria Fatima Hati; Yanuarius Bria Seran; Yuventius Tamelab; Marsela Luruk Bere (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
This research was conducted on grade 2B students of SDI Harekakae. The type of research used is classroom action research (CAR) which refers to Kurt Lewin's model. The main concept of Lewin's Action Research Model consists of four components, namely: planning, action, observation, and reflection. The data collection techniques in this study were observation, tests, and documentation, and the data analysis technique used was descriptive qualitative analysis. Based on the results of observations in cycle I, it shows that the average of only 10.25 students (51.25%) were active in the teaching and learning process. This indicates that students' activeness in learning is still lacking. However, the results of observations in cycle II show that on average almost all students were active in the teaching and learning process, increasing to 18.75 students (93.75%). In accordance with the learning outcomes of cycle I, it can be seen that the students' learning outcomes in cycle I have not yet reached or have not been able to meet the minimum completeness criteria determined, which is 80%. After making improvements in cycle II, there is a very significant increase where from the learning outcomes in cycle I only 11 students (55%) were complete, then in cycle II students who were complete according to the Minimum Completeness Criteria as many as 18 students (90%). This indicates that students who have completed the learning in cycle II have exceeded or answered the success indicator of 90% of the predetermined success indicator is 80%.